The economic impact of a new animal disease:same effects in developed and developing countries? - Rich, Karl M.; Niemi, J.K (World Organisation for Animal Health, 2017)
Animal disease outbreaks generate a range of economic and non-economic impacts. While a significant number of research studies have estimated the effects of various diseases in a variety of contexts, examining the differential impacts and implications associated with the introduction of a novel disease into a developing country, as opposed to a developed one, is a rich area for further research. In this paper, the authors highlight some of the key dimensions and implications associated with the impacts of new diseases, how they differ in different contexts, and their implications for public policy